The acute vitreous haemorrhage. - Lean, J S (1980)
One hundred cases of acute vitreous haemorrhage have been analysed prospectively. It was possible to identify the cause of the haemorrhage at presentation in 79% of the cases. 40% were due to retinal tears and only 6% were associated with diabetic retinopathy.